Comparison of Student Math Learning Outcomes Between Spiral Methods and Lecture Methods Set Material - Lastri Lastri; Rizal Kamsurya; Marwa Astriani Kamsurya (Indo-MathEdu Intellectuals Journal, 2022)
Learning mathematics at Muhammadiyah Ambon Junior High School tends to be monotonous and does not motivate students. The teacher in his learning only conveys the material he teaches, regardless of the level of understanding of the student. One of the better ways that can encourage students to be actively involved in finding concepts in the teaching and learning process is to do learning using a spiral approach. With a spiral approach in teaching and learning activities oriented to students. The learning process starts from the easy and concrete and goes into the difficult or abstract. That way, it will train the mindset of students in solving every problem in the world of mathematics. This research aims to find out the differences in student learning outcomes between students who are taught using the spiral method and the teaching method of the concept of class VII of Muhammadiyah Ambon Junior High School. The type of research used is quantitative with a sample of 56 people consisting of a control class of 28 people and an experimental class of 28 people. The instruments used are tests and observations. Tests are used to determine the learning outcomes of students who are taught using lecture methods and spiral and observation methods are used to find out the learning conditions that take place. The data analysis technique used is to use two-party t-tests. Based on the results of the data analysis, it was obtained that there were differences in student learning outcomes between students who were taught using spiral methods and lecture methods of the concept of class VII of Muhammadiyah Ambon Junior High School. The results are based on the results of hypothesis testing conducted using the t-test with the result of thitung obtained a value of 7.024. While the conversion result based on the t value distribution table is in the two-party test, obtained a ttabel value of 2.000.